Sistem Pendukung Keputusan Pemilihan Asuransi Dengan Metode Weighted Product Dan Weighted Sum Model - Ivan NUSANTARA siagian; Sulindawaty Sulindawaty; Bosker NUSANTARA Sinaga (Jurnal Mantik Penusa, 2017)
Development Insurance business today can make potential customers confused in determining or choosing the type of insurance that suits their needs and desires. This is what makes insurance agents hard to get customers because they can not give advice or alternatives for prospective customers, so the level of productivity decreases. Computer-based decision support systems can be used to help solve problems in terms of assisting everyone in making choices. The method used in the selection of life insurance is the Weighted Product Method and Weighted Sum Model, where each alternative provided will be done ranking to get the best results. Results resulting in the sorting of data life insurance products that serve as a tool in decision-making for prospective customers. The built system is expected to help prospective customers and agents in choosing the right life insurance and according to customer needs.